LETM1: A Single Entity With Diverse Impact on Mitochondrial Metabolism and Cellular Signaling - Natarajan, Gayathri K.; Mishra, Jyotsna; Camara, Amadou K. S.; Kwok, Wai-Meng (Frontiers in Physiology, 2021)
Nearly two decades since its discovery as one of the genes responsible for Wolf-Hirschhorn Syndrome (WHS), the primary function of the leucine-zipper EF-hand transmembrane 1 (LETM1) protein in the inner mitochondrial membrane (IMM) or the mechanism by which it regulates mitochondrial Ca2+ handling is unresolved. Meanwhile, LETM1 has been associated with the regulation of fundamental cellular processes such as development, cellular respiration and metabolism, and apoptosis. This mini-review summarizes the diversity of cellular functions impacted by LETM1 and highlights the multiple roles of LETM1 in health and disease.